Approaches for additive manufacturing of 3D electronic applications - Hörber, Johannes; Glasschroeder, J.; Pfeffer, Michael; Schilp, J.; Zaeh, Michael; Franke, Jörg (Procedia CIRP, 2014)
Additive manufacturing processes typically used for mechanical parts can be combined with enhanced technologies for electronics production to enable a highly flexible manufacturing of personalized 3D electronic devices. To illustrate different approaches for implementing electrical and electronic functionality, conductive paths and electronic components were embedded in a powder bed printed substrate using an enhanced 3D printer. In addition, a modified Aerosol Jet printing process and assembly technologies adapted from the technology of Molded Interconnect Devices were applied to print circuit patterns and to electrically interconnect components on the surface of the 3D substrates. ©2014 Elsevier B.V. This is an open access article under the CC BY-NC-ND license.
CRIS-Team Scopus Importer:2023-03-07
Keywords: 3D electronic devices; Additive manufacturing; Aerosol Jet printing; Integration; Powder bed-based printing; Printed electronics